Communication for Sustainable Development and Social Change. A brief overview - Servaes, Jan (CIC. Cuadernos de Información y Comunicación, 2012)
This article presents an overview of the theoretical changes in the perspective on development communication (at a general level: modernization, dependency, multiplicity; at the level of communication: diffusion versus participation). It attempts to position these changes within an historical assessment of the research and policy debate of the last 60 years. As a result, different methodologies and terminologies have evolved, which often make it difficult for development aid agencies, even though they share a common commitment to the overall goals of development communication to identify common ground, arrive at a full understanding of each other’s objectives, or to co-operate effectively in operational projects. The article will outline the key challenges ahead for the future of the field of Communication for Sustainable Development and Social Change (CSSC).